Beyond the Grid: An In-depth Analysis of Economic, Demographic, and Technological Drivers of Energy Poverty in 11 Developing Countries - Aqdas, Ramaisa; Ishak, Wan Zhalkiatul Aida Binti; Salman, Syed Muhammad; Sultan , Rashid (iRASD Journal of Economics, 2024)
This research examines the impact of critical factors, including GDP, population, internet, renewable power, human capital, and global link, on energy poverty in the New-11 nations, using a Panel ARDL technique. Energy poverty rises with GDP and population growth but is significantly reduced by internet access and renewable energy. Human resources and globalization present a mix of insignificant functions. Short-run illustrations depict initial movement in the long run, which abruptly stabilizes as renewable energy costs become apparent. The implications of the findings of energy poverty are the essential and inescapable policy calls for targeted investments in digitalization, sustainable energy, people, and intelligent globalization.